2022
DOI: 10.1021/acs.jpclett.2c02378
|View full text |Cite
|
Sign up to set email alerts
|

Hot Carrier Transfer in PtSe2/Graphene Enabled by the Hot Phonon Bottleneck

Abstract: The charge transfer (CT) process of two-dimensional (2D) graphene/transition metal dichalcogenides (TMDs) heterostructures makes the photoelectric conversion ability of TMDs into a wider spectral range for the light harvester and photoelectric detector applications. However, the direct in situ investigation of the hot carrier transport in graphene/TMDs heterostructures has been rarely reported. Herein, using the optical pump and a terahertz (THz) probe (OPTP) spectroscopy, the CT process from graphene to five-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 52 publications
0
2
0
Order By: Relevance
“…Later, in 2022, Quan et al investigated this charge transfer method caused by carrier aggregation. It was found that it could be related to the charge transfer process caused by the thermal phonon bottleneck effect in graphene, with the analysis of the scattering time and the Smith parameter in the heterostructure, as shown in Figure 2b [105].…”
Section: Regulating Thz Pc In Gr/tmd Heterostructures By Photogatingmentioning
confidence: 99%
“…Later, in 2022, Quan et al investigated this charge transfer method caused by carrier aggregation. It was found that it could be related to the charge transfer process caused by the thermal phonon bottleneck effect in graphene, with the analysis of the scattering time and the Smith parameter in the heterostructure, as shown in Figure 2b [105].…”
Section: Regulating Thz Pc In Gr/tmd Heterostructures By Photogatingmentioning
confidence: 99%
“…Previous reports have shown, however, that in graphene/TMD (including MoS 2 , WS 2 , WSe 2 , and PtSe 2 ) heterostructures, carriers can be promoted from graphene to TMDs under subbandgap excitation (that is, only graphene is excited). [21,30,[39][40][41] This is attributed to hot carriers generated after carrier-carrier scattering in graphene, which have sufficient energy to be transferred to the CB of TMDs. We believe that the same mechanism can account for our experimental observation, i.e., the hot electrons in the CB of PtSe 2 are transferred to the CB of MoS 2 immediately after optical excitation.…”
Section: Primary Hot Carrier Transfermentioning
confidence: 99%